DENTURE STOMATITIS: AN OVERVIEW OF EPIDEMIOLOGY, ETIOLOGY, AND CURRENT THERAPEUTIC STRATEGIES - Sumitro, Sumitro; Cuan, How Kim; Halim, Susanna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
ABSTRACT Denture stomatitis (DS) is a prevalent inflammatory condition of the oral mucosa, frequently observed in individuals wearing removable dentures. The condition is primarily initiated by the colonization of Candida species, though its development is often accelerated by other predisposing factors, making it a multifactorial clinical challenge. This article provides a comprehensive overview of the condition by focusing on a systematic review of the most recent scientific literature published from 2020 onward. The research methodology involved a systematic search across multiple scientific databases to gather current data on the epidemiology, etiology, risk factors, and contemporary therapeutic approaches for DS. The results from this review indicate a high prevalence of the condition, with a notable incidence among elderly patients and individuals with specific systemic health issues. The findings confirm that effective management necessitates a multifaceted strategy, combining conventional antifungal agents, innovative approaches like photodynamic therapy, and strict adherence to enhanced denture hygiene protocols. In conclusion, the successful treatment of denture stomatitis is not a one-size-fits-all solution; it requires an individualized therapeutic plan that is carefully tailored to each patient's specific risk factors and the underlying etiology of their condition. ABSTRAK Stomatitis gigi tiruan (DS) merupakan kondisi peradangan yang umum terjadi pada mukosa mulut, yang sering terjadi pada orang yang memakai gigi tiruan lepasan. Kondisi ini terutama dipicu oleh kolonisasi spesies Candida, meskipun perkembangannya sering kali dipercepat oleh faktor predisposisi lain, sehingga menjadikannya tantangan klinis multifaktorial. Artikel ini memberikan gambaran umum yang komprehensif tentang kondisi tersebut dengan berfokus pada tinjauan sistematis literatur ilmiah terbaru yang diterbitkan sejak tahun 2020 dan seterusnya. Metodologi penelitian melibatkan pencarian sistematis di berbagai basis data ilmiah untuk mengumpulkan data terkini tentang epidemiologi, etiologi, faktor risiko, dan pendekatan terapi kontemporer untuk DS. Hasil dari tinjauan ini menunjukkan prevalensi kondisi yang tinggi, dengan insidensi yang menonjol di antara pasien lanjut usia dan individu dengan masalah kesehatan sistemik tertentu. Temuan tersebut menegaskan bahwa manajemen yang efektif memerlukan strategi multifaset, yang menggabungkan agen antijamur konvensional, pendekatan inovatif seperti terapi fotodinamik, dan kepatuhan ketat terhadap protokol kebersihan gigi tiruan yang ditingkatkan. Sebagai kesimpulan, pengobatan stomatitis gigi tiruan yang berhasil bukanlah solusi yang cocok untuk semua orang; Hal ini memerlukan rencana terapi individual yang disesuaikan dengan faktor risiko spesifik setiap pasien dan etiologi yang mendasari kondisi mereka.